The Baganduang Boat Value-Based Learning Model in Elementary Schools - Darta Putra, Elpri; Maftuh, Bunyamin; Supriatna, Mamat (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to develop a learning model based on the value of baganduang boats to foster the character of eloklah budi elementary school students. This research is a research and development (R&D). The main steps in R&D research are: 1) Research and Information Collecting; 2) Planning, 3) Develop Preliminary Form a Product. 4) Preliminary Field Testing, 5) Main Product Revision, 6) Main Field Testing, 7) Operational Product Revision, 8) Operational Field Testing, 9) Final Product Revision, 10) Dissemination and Implementation. Data collection techniques in this study were interviews, observations, validity questionnaires, practicality questionnaires and pretest-posttest questions. The data analysis technique comes from opinions given by experts, teachers and students which are then carried out using the help of Nvivo software inported through qualitative data. The results of the analysis of the questionnaire of the practicality of the learning model based on the value of the beghanduang boat can be concluded that the learning model based on the value of the baghanduang boat according to students and teachers is included in the practical category and can be implemented for elementary school learning. It is hoped that the implementation of the Baganduang boat value-based learning model can help educators in developing a learning model based on local wisdom and can become a reference for other researchers.